Investigation of the relationship between food preferences and depression symptoms among undergraduate medical students: a cross-sectional study - Fatemeh Maleki Sedgi; Jalal Hejazi; Jalal Hejazi; Reza Derakhshi; Ghazal Baghdadi; Melinaz Zarmakhi; Mana Hamidi; Kamyar Mansori; Mohsen Dadashi; Mehran Rahimlou; Mehran Rahimlou (Frontiers in Nutrition)
IntroductionDepression is a psychological condition characterized by a persistent low mood. This study investigates the relationship between depressive symptoms and food preferences in undergraduate students.MethodsA cross-sectional design was employed among 502 students at Zanjan University of Medical Sciences. Data collection included validated questionnaires on food preferences, depression levels (Beck Depression Inventory), and physical activity (IPAQ), along with anthropometric measurements. Food preferences were analyzed for six groups: grains, fruits, vegetables, dairy, meat/fish, and snacks. Depression severity was categorized into six levels based on BDI scores: normal (1–9), mild (10–16), borderline (17–20), moderate (21–30), severe (31–40), and very severe (41–63). Depression risk was defined as the odds of belonging to a higher Beck Depression Inventory (BDI) category.ResultsParticipants with severe depression had lower preferences for grains, fruits, and vegetables but higher preferences for snacks. Adjusted analyses revealed that higher preferences for fruits (OR: 0.79; 95% CI: 0.68–0.98) and vegetables (OR: 0.81; 95% CI: 0.71–0.94) were significantly associated with reduced depression risk, while snack preferences increased risk (OR: 1.28; 95% CI: 1.03–1.68). However, the association between grain preferences and depression risk was not statistically significant after adjustment (OR: 0.82; 95% CI: 0.74–1.03).ConclusionThese findings highlight the bidirectional link between diet and mental health, underscoring the importance of dietary interventions in mental health strategies.